Awareness towards tobacco consumption: A community based study - Sah, R B; Shah, U; Subedi, L B; Jha, N (Journal of Chitwan Medical College, 2017)
More than 1 billion people worldwide smoke. If current trends continue, 8.4 million smokers are estimated to die annually of smoking-related deaths by the year 2020. To find out awareness towards tobacco consumption and to find out association between awareness towards tobacco and status of tobacco consumption among residents of Dhankuta municipality. The cross-sectional study was conducted among residents of Dhankuta Municipality where 205 households were taken as subjects. Pretested semi-structured questionnaire was administered to the study subjects and face to face interview was conducted. Chi-square test was applied to find out the association between awareness towards tobacco and status of tobacco consumption. Almost 41% of respondents were found to be aware of the harmful consequences of tobacco consumption. The respondents who did not consume tobacco was seen more aware of tobacco consumption (85.7%) than consuming tobacco (14.3%) (P<0.001).The respondents think the problem of tobacco consumption can be control by bann the production was significantly higher among those did not consuming tobacco (57.7%) than consuming tobacco (42.3%) (<0.001). Most of the respondents think smoking can be discourage by strict low (60.5%) followed by family support (24.9%) and education (20%) and recreational activities (8.8%). Awareness towards the harmful consequences of tobacco consumption was found to be less in Dhankuta Municipality. The problem of tobacco consumption can control by bann the production, awareness program and medicine i.e. nicotine therapy.